[Rezension von: Goldstein, Daniel M., 2016, Owners of the sidewalk. Security and survival in the informal city] - Ley, Lukas (Anthropos, 2018)
You could say that “Owners of the Sidewalk” is yet another book about the informal economy of a postcolonial city. Seasoned urban anthropologists should be warned that they will not be surprised by a new, groundbreaking theory of the informal or its politics. What this book offers can be summarized in a sentence: it explains the (re)production of the informal underbelly of a city, along with its problems of insecurity and violence, with special attention to clarity of writing and the politics of ethnography.